Biofotogrametric and electromyographic analysis in different position in women with temporomandibular disorder. - Silva, Muriel Priebe e; Milanesi, Jovana de Moura; Pasinato, Fernanda; Veron, Helenize; Antunes, Ana Gabrieli Ferreira; Corrêa, Eliane Castilhos Rodrigues (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The relationship established between TMJ (Temporomandibular Joint), cranium and cervical spine requires the synchrony of these structures for the proper performance of stomatognathic functions and muscle balance in this region. Objective: Evaluate the craniocervical posture and the electrical activity of masticatory and cervical muscles in sitting and standing positions in patients with TMD, correlating these variables. Method: The participants were 21 women, with mean age 28 ± 5.33 years and severe TMD. The participants were evaluated by electromyography of the masseter, anterior temporal and sternocleidomastoid (SCM) and upper trapezius muscles, bilaterally, in standing and sitting position. The body posture was evaluated by biophotogrammetry, with analysis of the Head Horizontal Alignment (HHA) and Acromion Horizontal Alignment (AHA) in frontal view and the Head Vertical Alignment (HVA) and Head Horizontal Alignment related to seventh cervical vertebra (HHAc7) in lateral view. Results: The electrical activity of masticatory muscles during resting did not differ between the different evaluated positions. During maximum intercuspation, the electrical activity was significantly lower in the left masseter (p=0.016), higher in the left anterior temporal muscle (p=0.046) and higher in the right (p=0.005) and left (p=0.015) upper trapezius muscles, in standing position when compared to sitting position. The photogrammetric values found were within the normal range. There was a significant and moderate negative correlation between the left SCM muscle and the right (r=0.386) and left (r=0.428) HHAc7 angle. Conclusions: Muscular electrical activity was modified with the change between sitting and standing positions, with an increase in cervical muscle recruitment and asynchrony of the masticatory muscles. Thus, it can be inferred that there is a postural destabilization with possible head anteriorization during maximum intercuspation, reinforcing the relation of synergy between the masticatory and cervical muscles.